Analysis of Remote Sensing, Gravity, and Magnetotelluric Data on Geothermal Fields in Ogan Komering Ulu (OKU) District, South Sumatra - Okta Dwi Puspita; Reinaldi Juniarto; Sava Sintya Larasati; Hafiz Hamdalah; Iqbal Takodama (Universitas Negeri Malang, 2020)
Geothermal energy is a clean alternative energy resource. Southern Ogan Komering Ulu (OKU), South Sumatera, is a geothermal prospect area because of the interaction between the Eurasian and Indo-Australian tectonic plates. It causes geological structures growth and the activity of volcanism in the area. Based on geological data, geothermal in southern OKU is indicated by the existence of 40–93 ºC temperature hot springs. Geological data based on remote sensing methods can determine the lineament. Geophysical data with gravity and magnetotelluric can identify the type of rock and the subsurface geological structure based on rock density and resistivity. Based on geological and gravity data indicates the presence of geological formations lead northwest-southeast, which is estimated as the geothermal fluid pathway with the suitability to the location of hot springs. The magnetotelluric data shows the geothermal reservoir rocks (clastic sedimentary rock) located at (-500)–(-2.500) meters depth with 30–200 Ωm resistivity. DOI: http://dx.doi.org/10.17977/um024v5i12020p022